EMG-triggered electrical stimulation is a feasible intervention to apply to multiple arm muscles in people early after stroke, but does not improve strength and activity more than usual therapy: a randomized feasibility trial. (May 2014) - Dorsch, Simone; Ada, Louise; Canning, Colleen G
Objective: To determine whether EMG-triggered electrical stimulation applied to multiple muscles daily is a feasible intervention and to determine its effect on strength and activity in very weak stroke patients. Design: A prospective, randomized trial with blinded assessment. Setting: Metropolitan mixed acute and rehabilitation units. Participants: Thirty-three people within four weeks of a stroke with less than Grade 3 strength in three out of four muscle groups (shoulder flexors, elbow extensors, wrist and finger extensors and thumb abductors) of the affected arm. Interventions: Participants were randomly allocated to receive EMG-triggered electrical stimulation to the four muscle groups of the affected arm plus usual therapy five times a week for four weeks, or usual therapy only. Main measures: Feasibility of the intervention was measured by examining compliance with the trial protocol. Strength was measured using manual muscle testing summed across muscle groups (0–20). Activity was measured using the Motor Assessment Scale, summed upper limb items (0–18). Results: The experimental group received 87% of the intervention. Following the intervention period, there was no difference between the groups for strength (mean between-group difference, 0 out of 20, 95% confidence interval (CI) −3 to 3, p = 0.91) or activity (mean between-group difference 1 out of 18, 95% CI −2 to 4, p = 0.44). Conclusions: It is feasible to apply EMG-triggered electrical stimulation to multiple muscles of the upper limb in very weak people early after stroke. However, it does not appear to improve strength or activity beyond usual arm therapy that contains strengthening.